CINDERELLA FORMULA IN CRAZY RICH ASIANS BY KEVIN KWAN - Tarumingkeng, Lietania Chikita; Maru, Mister Gidion; Maukar, Merlin M. (SoCul: International Journal of Research in Social Cultural Issues, 2024)
A story cannot be seperated from a formula. Formula is a structure of how the story told. Formula is a recipe need to follow by. This study discusses about Cinderella Formula in Kevin Kwan’s Crazy Rich Asians. The purpose of this study is to revealed Cinderella Formula in Crazy Rich Asians. The source of the data was taken from the movie script Crazy Rich Asians.The research design used in this study is qualitative research since the data is in form of words. The writer also used close reading approach to find the Cinderella Formula.The result of the research shows that there is the Cinderella Formula in the movie Crazy Rich Asians. This study is highly expected to give contribution for the reader so they can know and understand what Cinderella Formula really is.